Le paradoxe de la gestion des espaces verts : entre volonté de maîtrise et laissez-faire - Anna Rouadjia (VertigO)
The new ecological management of urban green spaces suggested by the principles of the sustainable development suppose not only a change of practices but also a transformation of representations over the urbanized nature. It is a question of passing of the control of the alive in the support and in the care of the nature. In Marseille, prevails paradoxically a non interventionist liberal urban politics which contradicts an urbanistic culture of the control and a taste for the order. Therefore, these new management policies turn out to be at the same time source of conflicts between local actors and an opportunity to value the image of the city. The social reception of these politics appears to the inhabitants like a pretext to justify the continuity of assimilated practices of arrangement to justify the continuity of practices of development likened to a disengagement of public authorities, which illustrates the more general backward movement of the place of the green spaces in town. This article aims at analyzing the obstacles to the emergence of this rising ecological culture, the instrumentalization of the terms of which tends to favor the maintenance of environmental disparities.